IMPLICATIONS OF TRANSLATION COMPETENCE IN THE LEGAL CONTEXT: A DIDACTIC PERSPECTIVE - KOŚCIAŁKOWSKA-OKOŃSKA, Ewa (Comparative Legilinguistics, 2017)
The paper addresses the existing models of translation competence that are relevant for didactics of legal translation. Translation competence is generally perceived as a theoretical construct embracing such areas as knowledge, skills and aptitudes that are vital for the performance of translation tasks. The paper shall start from concise presentation of most didactically relevant – in the author’s view – approaches to translation competence. This shall be followed by attempts aimed at the incorporation and integration of findings of competence research presented as well as practical solutions into the teaching and learning process with a view to legal translation competence.